Worlds of sleep - Brunt, Lodewijk; Steger, Brigitte (Frank & Timme, 2008)
Long description: A rikshaw as a bed? A mobile phone as a teddybear? Nightly struggles with bedbugs? Worlds of Sleep investigates the sleep patterns of babies and businessmen, of mothers and daughters, of the industrious and the idle. Read how mighty knights and zealous preachers value sleep, what medicine men and modern scholars think of it. Explore what disturbs lovers' sleep and how refugees ensure their restful slumber. The eleven chapters present fascinating new insights into the social and cultural variations of the dormant side of life around the globe.